Decreased effect of insulin to stimulate skeletal muscle blood flow in obese man. A novel mechanism for insulin resistance. - Laakso, M (1990)
Obesity is characterized by decreased rates of skeletal muscle insulin-mediated glucose uptake (IMGU). Since IMGU equals the product of the arteriovenous glucose difference (AVGd) across muscle and blood flow into muscle, reduced blood flow and/or tissue activity (AVGd) can lead to decreased IMGU. To examine this issue, we studied six lean (weight 68 +/- 3 kg, mean +/- SEM) and six obese (94 +/- 3 kg) men. The insulin dose-response curves for whole body and leg IMGU were constructed using the euglycemic clamp and leg balance techniques over a large range of serum insulin concentrations. In lean and obese subjects, whole body IMGU, AVGd, blood flow, and leg IMGU increased in a dose dependent fashion and maximal rates of all parameters were reduced in obese subjects compared to lean subjects. The dose-response curves for whole body IMGU, leg IMGU, and AVGd were right-shifted in obese subjects with an ED50 two- to threefold higher than that of lean subjects for each parameter. Leg blood flow increased approximately twofold from basal 2.7 +/- 0.2 to 4.4 +/- 0.2 dl/min in lean, P less than 0.01, and from 2.5 +/- 0.3 to 4.4 +/- 0.4 dl/min in obese subjects, P less than 0.01. The ED50 for insulin's effect to increase leg blood flow was about fourfold higher for obese (957 pmol/liter) than lean subjects (266 pmol/liter), P less than 0.01. Therefore, decreased insulin sensitivity in human obesity is not only due to lower glucose extraction in insulin-sensitive tissues but also to lower blood flow to these tissues. Thus, in vivo insulin resistance can be due to a defect in insulin action at the tissue level and/or a defect in insulin's hemodynamic action to increase blood flow to insulin sensitive tissues.